Altered Trek-1 Function in Sortilin Deficient Mice Results in Decreased Depressive-Like Behavior - Moreno, Sébastien; Devader, Christelle M.; Pietri, Mariel; Borsotto, Marc; Heurteaux, Catherine; Mazella, Jean (Frontiers in Pharmacology, 2018)
The background potassium channel TREK-1 has been shown to be a potent target for depression treatment. Indeed, deletion of this channel in mice resulted in a depression resistant phenotype. The association of TREK-1 with the sorting protein sortilin prompted us to investigate the behavior of mice deleted from the gene encoding sortilin (Sort1-/-). To characterize the consequences of sortilin deletion on TREK-1 activity, we combined behavioral, electrophysiological and biochemical approaches performed in vivo and in vitro. Analyses of Sort1-/- mice revealed that they display 1) a corticosterone-independent anxiety-like behavior, 2) a resistance to depression as demonstrated by several behavioral tests and 3) an increased activity of dorsal raphe nucleus neurons. All these properties were associated with TREK-1 action deficiency consequently to a decrease of its cell surface expression and to the modification of its electrophysiological activity. An increase of BDNF expression through activation of the furin-dependent constitutive pathway as well as an increase of the activated BDNF receptor TrkB were in agreement with the decrease of depressive-like behavior of Sort1-/- mice. Our results demonstrate that the TREK-1 expression and function are altered in the absence of sortilin confirming the importance of this channel in the regulation on the mood as a crucial target to treat depression.